DETERMINANTS OF UNMET NEED AMONG COUPLES OF REPRODUCTIVE AGE IN RW 07, KARUNRUNG VILLAGE, RAPPOCINI DISTRICT, MAKASSAR CITY - Ogesti, Tri; Azis, Rahmawati (PT. Jurnal Center Indonesia Publisher, 2026)
Unmet need refers to couples of reproductive age who wish to delay pregnancy or no longer desire children but are not using any contraceptive method. This study aimed to identify the relationship between knowledge, attitudes, and husband’s support with the incidence of unmet need among couples of reproductive age in RW 07, Karunrung Village, Rappocini District, Makassar City. The research was conducted from August to September 2022 using a purposive sampling technique with a total of 110 respondents. Data were collected through a structured questionnaire and analyzed using the Chi-Square test with SPSS version 26, and the findings were presented in distribution tables with descriptive explanations. The results showed significant associations between knowledge (p = 0.026), attitudes (p = 0.000), and husband’s support (p = 0.000) with the incidence of unmet need among couples of reproductive age. These findings highlight the importance of strengthening health education efforts and increasing husband involvement to reduce unmet need among couples of reproductive age.